Assessing the role of oxygen on ring current formation and evolution through numerical experiments. Issue 6 (16th June 2015) - Ilie, R.; Liemohn, M. W.; Toth, G.; Yu Ganushkina, N.; Daldorff, L. K. S.
Abstract: We address the effect of ionospheric outflow and magnetospheric ion composition on the physical processes that control the development of the 5 August 2011 magnetic storm. Simulations with the Space Weather Modeling Framework are used to investigate the global dynamics and energization of ions throughout the magnetosphere during storm time, with a focus on the formation and evolution of the ring current. Simulations involving multifluid (with variable H + /O + ratio in the inner magnetosphere) and single‐fluid (with constant H + /O + ratio in the inner magnetosphere) MHD for the global magnetosphere with inner boundary conditions set either by specifying a constant ion density or by physics‐based calculations of the ion fluxes reveal that dynamical changes of the ion composition in the inner magnetosphere alter the total energy density of the magnetosphere, leading to variations in the magnetic field as well as particle drifts throughout the simulated domain. A low oxygen to hydrogen ratio and outflow resulting from a constant ion density boundary produced the most disturbed magnetosphere, leading to a stronger ring current but misses the timing of the storm development. Conversely, including a physics‐based solution for the ionospheric outflow to the magnetosphere system leads to a reduction in the cross‐polar cap potential (CPCP). The increased presence of oxygen in the inner magnetosphere affects the global magnetospheric structure and dynamics and brings the nightside reconnection point closer to the Earth. The combination of reduced CPCP together with the formation of the reconnection line closer to the Earth yields less adiabatic heating in the magnetotail and reduces the amount of energetic plasma that has access to the inner magnetosphere. Key Points: Low O + /H + ratio produced stronger ring current Inclusion of physics‐based ionospheric outflow leads to a reduction in the CPCP Oxygen presence is linked to a nightside reconnection point closer to the Earth